2015
DOI: 10.1503/cmaj.150564
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with planned place of birth among women with low-risk pregnancies

Abstract: Background:Previous studies have shown that planned home birth is associated with a decreased likelihood of intrapartum intervention with no difference in neonatal outcomes compared with planned hospital birth. The purpose of our study was to evaluate different birth settings by comparing neonatal mortality, morbidity and rates of birth interventions between planned home and planned hospital births in Ontario, Canada. Methods:We used a provincial database of all midwifery-booked pregnancies between 2006 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
4
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 7 publications
8
53
4
7
Order By: Relevance
“…Further work is required. It is important to note that overall prevalence of intervention was higher in the hospital cohort (augmentation, epidural analgesia, assisted vaginal, and cesarean birth), which supports international literature on lower intervention rates in out‐of‐hospital births 7, 10, 13…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Further work is required. It is important to note that overall prevalence of intervention was higher in the hospital cohort (augmentation, epidural analgesia, assisted vaginal, and cesarean birth), which supports international literature on lower intervention rates in out‐of‐hospital births 7, 10, 13…”
Section: Discussionsupporting
confidence: 76%
“…Hutton et al's much larger study of 11,493 planned home births in Ontario had a 24.4% rate of hospital transport, which was significantly lower in multiparous women (14.3%) than in nulliparous women (45.6%) 13. Ontario birth center overall transport rates were higher than Hutton et al's study but were lower for nulliparous women.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, international studies showed a significantly lower risk of episiotomy [12, 13], pharmacological pain management [1215], assisted vaginal birth [12, 13], caesarean section [12, 13], and augmentation of labour [1215] in birth settings other than obstetric units, although in one study no difference in rate of instrumental births was found [15]. …”
Section: Introductionmentioning
confidence: 99%
“…However, these studies have been conducted in countries with relatively low home birth rates, not exceeding 7% [12, 13, 15]. In the Netherlands, home birth has traditionally been part of the established maternity care system.…”
Section: Introductionmentioning
confidence: 99%